Attitudes towards PEF and environmental labeling in the Nordic agri-food sector - case studies - Woodhouse, Anna; Krewer, Christoffer; Hietala, Sanna; Möller, Hanne; Kristensen, Troels (Nordic Council of Ministers, 2019)
The PEF guide was developed as one of the building blocks of the Flagship initiative of the Europe 2020 Strategy – “A Resource-Efficient Europe". In April 2013 the Commission adopted Recommendation 2013/179/EU on the use of common methods to measure and communicate the life cycle environmental performance of products and organisations, which had the Product Environmental Footprint (PEF) Guide5 as its annex. The aim was to establish a common methodological approach to enable EU member states to assess, display and benchmark the environmental performance of products, services and organisations. The PEF methodology is based on Life Cycle Assessment (LCA) and the 16 environmental impact categories included are relying on scientifically sound impact assessment methods that are agreed at international level. The PEF project is in its transition phase and an implementation phase is the next step. Included in the implementation of PEF is the communication of PEF results to consumer (B2C) and business to business (B2B) communication. A labelling scheme has been identified as one potential way of communicating PEF to consumers. However, before a label can be decided upon and communicated, the PEF methodology needs to be known and accepted by stakeholders along the Nordic agri-food chain. The Nordic Environmental Footprint (NEF) group requested the NordPEF group to examine the attitudes to PEF as concept and how PEF can effectively be explained to consumers and farmers so that they accept the need for such type of information for their decision making. The NEF group also called for the NordPEF group to perform a more in-dept expert analysis of how environmental properties of food and other agriculture products may be communicated to the stakeholders; identifying possible barriers, how environmental information is communicated today and with what results, and if there is a need for a PEF label. The EC report on communication “Assessment of different communication vehicles for providing Environmental Footprint information” from 2011 formed a basis to the work performed in this project. To be able to understand the attitude, opportunities and barriers towards using PEF results in the communication among stakeholder’s interviews were conducted in each Nordic country (SE, DK, NO, FI) with agri-food stakeholders along the supply chain.
Keywords: PEF; Labeling; environmental footprint; life cycle analysis; LCA